The Impact of Entrepreneurship Perceptions on Entrepreneurial Intention During the COVID-19 Pandemic - Li, Pei; Li, Bing; Liu, Ziyang (Frontiers in Education, 2021)
The global pandemic of COVID-19 is a challenge for entrepreneurship education in universities and various organizations. Although positive responses to overcome the challenges of COVID-19 are being made, entrepreneurship strategies and policies might not meet students’ requirements. In order to enrich education management research, the main aim of this study is to provide a conceptual model and examine the relationship between perceptions, perceived positive attitudes on entrepreneurship education, and entrepreneurial intention (EI) during the COVID-19 crisis. The model is tested by using data from universities that are located in Shanghai, P.R. China. The study reveals that (a) perceived social norms and perceived self-efficacy positively influence perceived positive attitudes in entrepreneurship education; (b) there is no relationship between perceived entrepreneurial barriers and perceived positive attitudes in entrepreneurship education; (c) perceived positive attitudes in entrepreneurship education positively influence EI. The findings contribute to university and government policies on the development of entrepreneurial education. The framework of this study provides insight into the influential factors of entrepreneurship education that contribute to theoretical studies in the COVID-19 pandemic.